PENGEMBANGAN E-MODUL PENGAYAAN ISOLASI DAN KARAKTERISASI BAKTERI SEBAGAI SUMBER BELAJAR BIOLOGI - Kismiati, Dyah Aniza (JURNAL BIOEDUCATION, 2020)
This study aims to determine the feasibility of an enrichment e-module of isolation and characterization as a source of learning biology. This type of research is a Research and Development study with ADDIE model with nonequivalent pretest posttest control group design. This product was validated by experts (two expert lecturers, three biology teachers, and three peer reviewers) and was also limit tested to 21 class XI students. The research sample for limited trials is 2 classes based on purposive sampling technique, Class X MIPA 5 as a control class and Class X MIPA 1 as an experimental class. The instrument used in this limited trial was a questionnaire with Guttman Scale. Data were analyzed descriptively. The results of the study showed that the E-module enrichment of isolation and characterization of categorized bacteria was very suitable to be used as a source of learning biology when viewed from the aspect of appearance (score 87.50), the program (score 85.72), learning (score 92.73), and correctness of content (score 95.45).Keywords: bacteria, biology, e-module, learning material.